03.04 Serum and synovial concentration of calprotectin in rheumatoid arthritis patients. (1st March 2017) - Shumnalieva, Russka; Velikova, Tsvetelina; Kachakova, Darina; Monov, Simeon; Tumangelova-Yuzeir, Kalina; Kyurkchiev, Dobroslav; Rashkov, Rasho
Abstract : Abstract: Calprotectin is a 36 kDa protein released from activated leukocytes during bacterial infection or inflammation. It is potentially a more sensitive biomarker of disease activity in rheumatoid arthritis (RA) as it directly reflects the local inflammation in the joints rather than systemic inflammatory activity. Objective: The aim of our study was to compare the systemic and local concentrations of calprotectin in RA and osteoarthritis (OA) patients and to establish a possible systemic and local biomarker for RA disease activity and severity. Material and methods: Concentrations of calprotectin were compared between matched serum and synovial fluid (SF) samples from 20 RA and 15 OA patients by using HK325 Human Calprotectin ELISA kit (Hycult biotech, USA). 16 healthy donors were used as controls. Results: Serum concentration of calprotectin was higher in RA compared to OA (344.25 ng/ml versus 209.33 ng/ml, p=0.002) and HCs (188.13 ng/ml, p=0.000) and there was a significant difference of its concentration between the three studied groups (p<0.001). Within the RA group levels of calprotectin were higher in SF compared to serum (p=0.000) and showed moderate correlation (r=0.595, p=0.006). The highest serum and SF concentration of calprotectin in RA was found in patients with disease duration between 7 and 24 months. The systemic concentration of calprotectin was higher in patients with positive rheumatoid factor type IgG and IgA and the local concentration of calprotectin was higher in patients with mild compared to moderate degree of synovial hypertrophy found by MSUS (p=0.025). Patients on corticosteroids had lower systemic and local concentration of calprotectin (p=0.027 and p=0.002, respectively). Conclusions: Systemic and local calprotectin levels correlate with clinical, immunological and instrumental assessments of disease activity and joint inflammation and disease under treatment. Calprotectin could be used as a possible biomarker for monitoring the disease activity and severity of RA. Larger sets are needed to confirm the diagnostic and prognostic accuracy of calprotectin in RA. Acknowledgement: The study was supported by Grant 61/2015 from Medical University-Sofia, Bulgaria